Critical Management of Recurrent Seizure at 16-Year-Old Primigravida with Atypical Eclampsia: A Case Report - Kamanjaya HS, Putu Ari; Febri Jaya Gunawan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Atypical eclampsia, characterized by seizures without the classic signs of hypertension and proteinuria, presents a diagnostic and therapeutic challenge in the critical management aspect. This case report highlights the critical management of recurrent seizures in a young primigravida with atypical eclampsia. Case presentation: A 16-year-old primigravida at 38 weeks gestation presented with recurrent generalized tonic-clonic seizures. Despite initial magnesium sulfate therapy, seizures persisted postpartum. The patient was managed with a combination of midazolam and dexmedetomidine for seizure control and sedation. After five days of intensive care, the patient recovered without further complications. Conclusion: This case underscores the importance of considering atypical eclampsia in pregnant women presenting with seizures, even in the absence of typical preeclampsia symptoms. The successful use of midazolam and dexmedetomidine in this case suggests their potential as alternative therapeutic agents for refractory seizures in eclampsia. Further research is needed to validate these findings and establish optimal treatment protocols for atypical eclampsia.